ORGANIZATIONAL AND METHODOLOGICAL ASPECTS OF DEVELOPMENT OF INTEGRATED ENVIRONMENTAL AND ECONOMIC POLICIES - Elena Shelukhina (Вестник Северо-Кавказского федерального университета, 2022)
The article considers the content and methodological aspects of development of environmental-economic accounting system from the standpoint of the system ofnational accounts, offered by the Department ofEconomic and Social Information and Policy Analysis of the United Nations Organization, attempts to form the balance of environmental accounting as the direction and implementation in practice of Russian organizations.